Bay‘ Mumtalakāt al-Waqf: Dirāsah Taḥliliyyah fī Ḍau’ Tashrī‘āt al-Waqf fī Hukumah Māliziyā - Ab Rahman, Muhamad Firdaus; Abdullah Thaidi, Hussein ‘Azeemi; Hamdan, Mohammad Naqib; Ab Rahim, Siti Farahiyah (AHKAM : Jurnal Ilmu Syariah, 2022)
This article aims to critically examine  the  issue  of  selling  waqf properties  in  Malaysia's  waqf  legislations.  This tudy  adopts  a  qualitative methodology  employing  field  work  data.  The  findings  indicate  that  even though the waqf fiqh provides a choice of periods to be either temporary or permanent waqf, the Malaysian Waqf laws adopt permanent waqf and prohibits the  temporary  waqf  for  the  sake  of  public  interest  (maslahah).  Therefore, waqf properties cannot be cancelled by a donor, and that waqf land cannot be sold, given as a present, or bequeathed. The finding established that the Waqf laws are consistent with the waqf's aims. Thus, this paper proposes that each  State's  Waqf  Corporation  and  Islamic  Religious  Council  in  Malaysia needs to conduct a review of the existing waqf rulings and legal framework to ensure that they are consistent with the waqf purpose for benefiting donors, waqf holdings, and beneficiaries.Keywords: sell; Waqf; Property; legislation; Malaysia  ملخ: تهدف هذه الورقة إلى دراسة المواد القانونية الشرعية المتعلقة ببيع ممتلكات الوقف في دولة ماليزيا. وتعتمد هذه الدراسة على المنهج النوعي مع استخدام المناهج الاستقرائية والوصفية والمقارنة والميدانية في تحليل البيانات. ومن أهم نتائج  هذه الورقة أن تشريعات الوقف لدولة ماليزيا لا تجيز الوقف المؤقت وانتهاء الوقف ورجوعه وبيعه، وهذا دليل على أن تشريعات الوقف في دولة ماليزيا تتفق مع مقاصد الوقف أنه لا يباع أصلها ولا يوهب ولا يورث، ويكون الوقف مستمرا غير مقطوع. وتقترح هذه الورقة تشجيع هيئات الأوقاف لكل ولاية في ماليزيا على تقويم المواد القانونية المنصوصة في قانون الوقف الحالي حتى تتفق مع مقاصد الوقف لمصلحة الواقفين والموقوف عليهم والأموال الموقوفة.  .يازيلام؛ فقو ؛نوناق ؛تاكلتمم ؛عيب :ةيحاتفلما تاملكلا